Efficacy of attenuated bacteria vaccine against streptococcal infection in larvae tilapia (Oreochromis niloticus) - Agus Suryahman; Andi Masriah; Khairun Nisaa; Rahmi; Akmal (Sekolah Tinggi Ilmu Pertanian Wuna, 2021)
One of the common diseases found in tilapia is a streptococcal disease caused by the Streptococcus agalactiae bacteria. Treatment of this disease is generally done by using antibiotics. The use of antibiotics in controlling disease in fish can create resistant bacterial strains with certain doses. The use of vaccines is one of the alternative control methods in fish defence against infections. The purpose of this study was to analyze the efficacy of vaccination on seeds through immersion using attenuated active bacteria to increase immunity at the beginning of the spread of streptococcosis disease. The vaccine used was obtained from attenuated Streptococcus agalactiae bacteria through repeated passage ten times. Vaccination was carried out through oral vaccine. Challenge tests were carried out on days 7, 14, and 21 days after vaccination on tilapia larvae by immersion. The result indicated that vaccination using attenuated bacteria could increase lysozyme activity at each observation time compared to control. The mortality of post-challenged larvae on days 7, 14 and 21 post-vaccination was lower than that of unvaccinated seed. The percentage of RPS values up to the 14th day of observation has increased and tends to decrease on the 21st day.